Strategi Komisi Aparatur Sipil Negara (KASN) dan Badan Pengawas Pemilu dalam Menjaga Netralitas Aparatur Sipil Negara (ASN) pada Masa Pilkada 2024 di Provinsi Sumatera Barat - Rahmadani Rahmadani; Muthia Fadhilla; Randi Kurniawan; Yulia Hanoselina (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The neutrality of the State Civil Apparatus (ASN) is an important foundation in carrying out government duties in Indonesia, especially during the Regional Head Election (Pilkada) process. ASN is expected to carry out their roles neutrally, impartially and adhere to the principles of justice, in accordance with the provisions in Law Number 5 of 2014 concerning ASN. This research aims to evaluate the role of the State Civil Apparatus Commission (KASN) and the Election Supervisory Agency (Bawaslu) in maintaining ASN neutrality in the 2024 Regional Head Election in Padang City. Using a qualitative approach, this research analyzes data taken from various legal documents, official reports, and information related to violations of ASN neutrality in previous elections. The results revealed that violations of ASN neutrality are still quite high and have the potential to increase in the 2024 Pilkada. KASN and Bawaslu have made a number of efforts, such as conducting socialization and conducting strict supervision, to prevent these violations. This study concludes that ASN neutrality plays an important role in realizing the principles of good governance and in ensuring the implementation of fair and democratic elections, free from conflicts of interest